HbA1c measured in stored erythrocytes is positively linearly associated with mortality in individuals with diabetes mellitus. - Diewertje Sluik (Public Library of Science (PLoS), 2012)
Introduction Observational studies have shown that glycated haemoglobin (HbA(1c)) is related to mortality, but the shape of the association is less clear. Furthermore, disease duration and medication may modify this association. This observational study explored the association between HbA(1c) measured in stored erythrocytes and mortality. Secondly, it was assessed whether disease duration and medication use influenced the estimates or were independently associated with mortality. Methods Within the European Prospective Investigation into Cancer and Nutrition a cohort was analysed of 4,345 individuals with a confirmed diagnosis of diabetes at enrolment. HbA(1c) was measured in blood samples stored up to 19 years. Multivariable Cox proportional hazard regression models for all-cause mortality investigated HbA(1c) in quartiles as well as per 1% increment, diabetes medication in seven categories of insulin and oral hypoglycaemic agents, and disease duration in quartiles. Results After a median follow-up of 9.3 years, 460 participants died. Higher HbA(1c) was associated with higher mortality: Hazard Ratio for 1%-increase was 1.11 (95% CI 1.06, 1.17). This association was linear (P-nonlinearity = 0.15) and persistent across categories of medication use, disease duration, and co-morbidities. Compared with metformin, other medication types were not associated with mortality. Longer disease duration was associated with mortality, but not after adjustment for HbA(1c) and medication. Conclusion This prospective study showed that persons with lower HbA(1c) had better survival than those with higher HbA(1c). The association was linear and independent of disease duration, type of medication use, and presence of co-morbidities. Any improvement of HbA(1c) appears to be associated with reduced mortality risk.